2011
DOI: 10.1002/cae.20337
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting effectiveness in e‐learning: An analysis in production management courses

Abstract: E-learning may help to open up new channels for the traditional teaching of engineering but there are many questions about what makes e-learning an effective and satisfactory method, in particular, in the field of industrial engineering. This article evaluates the potential factors affecting the effectiveness of engineering e-learning courses by applying structural equation modeling in a sample of students of multiple production management courses for industrial engineering students. This way, the gaps and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…Our results can be explained due to the fact that younger students are usually more computer savvy and more experienced with advanced technology (Martinez-Caro, 2009;Smith & Necessary, 1996). Although the technology was relative simple to use, it seems that in our study older students expected to receive better support from the teaching staff.…”
Section: Summary Discussion and Recommendationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Our results can be explained due to the fact that younger students are usually more computer savvy and more experienced with advanced technology (Martinez-Caro, 2009;Smith & Necessary, 1996). Although the technology was relative simple to use, it seems that in our study older students expected to receive better support from the teaching staff.…”
Section: Summary Discussion and Recommendationsmentioning
confidence: 83%
“…Studies have examined the factors that affect course design and training of lecturers (Kanuka, Rourke, & Laflamme, 2007;Liu & Lee, 2005), learner's perspectives, such as satisfaction (Gunawardena & Zittle, 1997), communication between colleagues (Hammond, 1999), technical skills (Ross, 1996), meaningful learning (Arbaugh, 2000;Barak & Dori, 2005;Martinez-Caro, 2009), and thinking skills (Barak & Dori, 2009;Barak & Rafaeli, 2004). Other studies have shown that online learning in higher education faces many challenges, and the effect of DL on the teaching and learning culture in academic institutions is still limited (Bonk, Wisher, & Lee, 2003;Cuban, Kirkpatrick, & Peck, 2001;Kali et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is a considerable volume of research related to the benefits of satisfaction in higher education. For example, satisfaction has been linked to student performance (Bean & Russell, 1986;Marks et al, 2005;Martínez-Caro, 2011), retention (Astin, 1993;Tinto, 1993;DeShields, Kara, & Kaynak, 2005), class attendance (Aitken, 1982;Bean, 1985;Spady, 1970), or student engagement (Kuh, 2003;Zhao & Kuh, 2004;Coates, 2005). Moreover, student satisfaction is often used to assess educational quality (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…E-learning can be viewed as synonymous with web-based learning, online learning, Internet-based training, or virtual learning (Khan, 2001). It can be considered as a teaching -learning process supported by information and communication technologies (ICTs), in which it is not necessary to have a physical meeting of teachers and students, and whose objective is to facilitate a flexible (at any time and place), interactive, and student-centred learning (Martínez-Caro, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most common method is satisfaction and performance (Martinez-Caro, 2009). Structure and design of the course have a key role in the learner satisfaction in online learning (Roach & Lemasters, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%